The mycobiota of the human body: a spark can start a prairie fire. (3rd July 2020) - Zhang, Di; Wang, Ying; Shen, Sunan; Hou, Yayi; Chen, Yugen; Wang, Tingting
ABSTRACT: Mycobiota are inseparable from human health, shaking up the unique position held by bacteria among microorganisms. What is surprising is that this seemingly small species can trigger huge changes in the human body. Dysbiosis and invasion of mycobiota are confirmed to cause disease in different parts of the body. Meanwhile, our body also produces corresponding immune changes upon mycobiota infection. Several recent studies have made a connection between intestinal mycobiota and the human immune system. In this review, we focus on questions related to mycobiota, starting with an introduction of select species, then we summarize the typical diseases caused by mycobiota in different parts of the human body. Moreover, we constructed a framework for the human anti-fungal immune system based on genetics and immunology. Finally, the progression of fungal detection methods is also reviewed.